An Aneurysmal Interatrial Septum with a Patent Foramen Ovale and Multiple Fenestrations Closed by A Single Occluder Device - Shokoufeh Hajsadeghi; Mitra Chitsazan; Mohammad Namazi; Mandana Chitsazan (Acta Medica Iranica, 2012)
The patent foramen ovale (PFO) usually is a very small potential opening in the atrial septum. Under the conditions of normal hemodynamics with higher left atrial than right atrial pressures, the septum primum is forced against the foramen by the higher left atrial pressure and there is no actual persistent opening through the foramen. However, with any, even transient, increase in right atrial pressure this flap or "valve" can be pushed away from the septum and forced open. This results in the shunting of blood and anything else in the right atrium from the right atrium to the left atrium. Often the "valve" of the foramen becomes redundant and develops an "aneurysm" of the atrial septum. A large, redundant septum primum can have several additional openings or "fenestrations" in it. The PFO is now can be treated by interventional percutaneous therapy. This case represents a 24-year-old male with an aneurysmal interatrial septum and patent foramen ovale associated with multiple fenestrations. The defects were closed by a single Amplatzer® septal occluder.